Az I. világháborút lezáró békeszerződés máig tartó hatása a Kárpát-medence vasúthálózatára - Bajor, Tibor (Közép-Európai Közlemények, 2016)
The Hungarian railway network with the latest and most advanced in the XIX–XX. at the turn of the century. The railway network plays a crucial role not only within the country’s borders, but the whole of Europe. The nationalities wanted to create their own state in the Austro - Hungarian monarchy. The Entente validate their own political and economic interests of the Páruzsi peace talks, was used for the national aspirations. The world changes strengthened the political aspirations of the Entente. The strategic interests also justify their decisions. Soviet Russia and the European labor movement organization of great danger to the Entente countries. Politicians of the Entente countries have developed the boundaries of the Central European countries, on the basis of these two reasons. They split up the single railway network in small units. Austria wants now to standardize the components, according to their own interests. Hungary can not promote their own interests in the field of European rail services.